Improving the rights of persons with disabilities in Malaysia through Sustainable Development Goals (SDG) - Md Tah, Ikmal Hisham; Mokhtar, Khairil Azmin (Zes Rokman Resources, 2018)
The introduction of 2030 Agenda and Sustainable Development Goals (SDG) has significantly improved the rights of persons with disabilities at the global stage. The SDG has created the opportunity in progressing their rights to the next level especially after the inception of the United Nations (UN) Convention on the Rights of Persons with Disabilities (CRPD). This paper addresses the link between SDG and CRPD where Malaysia has become one of the parties that ratified the CRPD. This link is crucial in order to improve the living condition and rights of persons with disabilities in Malaysia. Based on the analysis done in this paper several issues have been identified, and a few challenges have been anticipated which must be cautiously observed by all stakeholders in improving the rights of disabled people. Among those include the non-legal effect of SDG and no monitoring mechanism available for disabled organizations to observe the progress in realising the rights. Therefore, it is crucial for government and various stakeholders related to disability issues to observe the importance of SDG in improving the rights of this minority groups and allowed them to be inclusive within society.